Influência de atividades lúdico-desportivas na realização de equoterapia em pacientes neurológicos - ensaio clínico controlado aleatorizado - Sousa, Fernando Henrique de [UNESP]; Navega, Marcelo Tavella [UNESP] (University Nove de Julho, 2012)
Introduction: Equine therapy is a therapy that uses horses to provide the practitioner in rehabilitation aspects of motor, sensory, behavioral and social. Objective: To investigate the effect of the combination of playful activities with hippotherapy sessions on the trunk balance and range of motion. Methods: We selected 18 practitioners diagnosed with cerebral palsy were randomly divided into two groups. The group 1 held hippotherapy sessions, and group 2 held equine therapy with recreational activities and sports. Before and after treatment, the trunk control and range of motion of the practitioners were evaluated. The data were analyzed using the Student’s t-test (p <0.05). Results: There was an improvement in range of motion and balance in both groups. Conclusion: Equine therapy is an effective treatment for individuals with cerebral palsy, regardless of accomplishing it with or without recreational activities.

Introdução: A Equoterapia é uma terapia que utiliza o cavalo para proporcionar ao praticante a reabilitação nos aspectos motores, sensoriais, comportamentais e sociais. Objetivo: Verificar o efeito da associação de atividades lúdicas com as sessões de Equoterapia sobre o equilíbrio de tronco e amplitude de movimento. Métodos: Foram selecionados 18 praticantes com diagnóstico de paralisia cerebral, divididos aleatoriamente em dois grupos. O grupo 1 realizou sessões de Equoterapia; e o grupo 2, Equoterapia com atividades lúdico-desportivas. Antes e após o tratamento, foram avaliados o controle de tronco e a amplitude de movimento dos praticantes. Os dados encontrados foram analisados utilizando o teste estatístico “t” de Student (p<0,05). Resultados: Houve melhora na amplitude de movimento e no equilíbrio nos participantes de ambos os grupos. Conclusão: A Equoterapia é um recurso eficaz para o tratamento de indivíduos com paralisia cerebral, independentemente de ser realizada com ou sem atividades lúdicas.
Influence of recreational and sports activities in the conduct of hippotherapy in neurological patients – randomized controlled trial